Penerapan Metode AHC (Agglomerative Hierarchical Clustering) untuk Klasifikasi Habitat Bentik di Desa pengudang, Kabupaten Bintan - Ulfatul Syahara; Esty Kurniawati; Mario Putra Suhana; Rika Anggraini; Falmi Yandri (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Pengudang village is one of the villages located in Bintan Regency, Riau Islands Province which has a diverse marine ecosystem, in which there are various types of benthic habitat. This research aims to classify the benthic habitat in Pengudang Village and determine the diversity and characteristics of the bottom water substrate at the research location. This research was carried out on 10-11 June 2023 in Pengudang village with a total of 224 research points. This research uses data collection techniques using the random sampling method, then continues with data analysis using the AHC (agglomerative hierarchical clustering) method. The results of the research applying the AHC (agglomerative hierarchical clustering) method for the classification of benthic habitats resulted in six types of benthic habitats which, after being analyzed using the AHC method, resulted in seven habitat classifications that dominated all research points, the first class contained sand, dead coral and benthic habitat types. live coral, the second class is benthic habitat types of seagrass and sand, the third class is benthic habitat types of seagrass and sand, the fourth class is benthic habitat types of live coral, dead coral, seagrass, algae and sand, the fifth class is the type of habitat benthic live coral, dead coral, algae and sand, the sixth class of benthic habitat types of algae and sand, and the seventh class of benthic habitat types of live coral, dead coral and sand.